LEGAL BASIS OF RELATIONS BETWEEN RELIGIOUS ORGANIZATIONS AND CIVIL SOCIETY INSTITUTES - Firuz Tuygunovich Rashidov (American Journals, 2025)
This article discusses the relations between the state, religion, and religious organizations , the lawful activities of religious organizations , the need to improve their role within the system of civil society institutions , the procedure for establishing religious organizations under the legislation of the Republic of Uzbekistan; and the content and key directions of the state policy in the religious sphere and the concept of ensuring citizens' freedom of conscience in the Republic of Uzbekistan.
Keywords: Religious organization, civil society, law, concept, spiritual heritage, confession, human, rights, democracy.